2013
DOI: 10.1186/1471-2318-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of commonly prescribed medications potentially contributing to urinary symptoms in a cohort of older patients seeking care for incontinence

Abstract: BackgroundSeveral medication classes may contribute to urinary symptoms in older adults. The purpose of this study was to determine the prevalence of use of these medications in a clinical cohort of incontinent patients.MethodsA cross-sectional study was conducted among 390 new patients aged 60 years and older seeking care for incontinence in specialized outpatient geriatric incontinence clinics in Quebec, Canada. The use of oral estrogens, alpha-blocking agents, benzodiazepines, antidepressants, antipsychotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 29 publications
2
33
3
2
Order By: Relevance
“…It is of interest, however, that 57 % of the patients did indeed take drugs that could trigger or at least promote incontinence. The study of Kashyap et al revealed a similar result whereby the prevalence of drug consumption with an impact on the lower urinary tract amounted to 61% [6]. This means that more than half of the patients regularly took one or more drugs that could, on their own, be the sole reason for their incontinence.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…It is of interest, however, that 57 % of the patients did indeed take drugs that could trigger or at least promote incontinence. The study of Kashyap et al revealed a similar result whereby the prevalence of drug consumption with an impact on the lower urinary tract amounted to 61% [6]. This means that more than half of the patients regularly took one or more drugs that could, on their own, be the sole reason for their incontinence.…”
mentioning
confidence: 90%
“…The quality of life of the afflicted persons is appreciably impaired and therapy for overactive bladder syndrome leads to a significant improvement in the quality of life [5]. Polypharmacy is one of the reversible causes of overactive bladder [6]. We speak of polypharmacy when five or more drugs are taken regularly [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Medications that interfere with cerebral processing of bladder function and/or have cholinergic effects on the smooth muscles, such as antidepressants, antipsychotic, and sleep medications, can exacerbate UI. 37 …”
Section: Epidemiology and Clinical Presentation Of Urologic Diseases mentioning
confidence: 99%
“…Potential mechanisms include an increase in urine production (e.g., loop diuretics), interference with sphincter function (e.g., alpha-blocking agents), disruption of detrusor contractility (e.g., anticholinergic medication) and interference with cerebral control of micturition (e.g., sedative/hypnotic medication such as benzodiazepines). 4 Drug-drug interactions may also cause pharmacokinetic or pharmacodynamic alterations, leading to unexpected toxicity or therapeutic failure.…”
Section: Polypharmacymentioning
confidence: 99%